The tradition of compiling academic grammar in some languages: scientific apparatus, structure and design - Momynova Б.; Slyambekov Қ. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2022)
Academic grammar is the grammar of a single language, where the main research results of prominent scientists who have studied the grammar of a language and raised it to a scientific level, a set of popular scientific thoughts and conclusions in the fundamental works of leading scientists of a particular language are concentrated. Academic grammar is based on the language systems of conglomerates, not as separate, but closely and organically related to each other, related words, forms of words, phrases, sentences, etc. For example, we can solve some complex morphology issues by considering them on the basis of syntax and word formation, as well as against the background of phonetics and phonologies. As well as the meaning of some grammatical meanings are revealed in more detail through the lexical meaning. The lexical level of the language will also help solve difficult grammar issues, including morphology, in particular. Language is a system, language is integrity. The establishment of grammatical norms and the display of rich expressive possibilities is based on the presentation of the entire grammatical system of the modern «Qazaq grammar». The tradition of writing grammar, which began more than 2500 years ago in the history of mankind, continues to this day. Today, in the CIS countries, the publication of academic grammar has become a large-scale direction. Grammar compounding has different traditions and techniques of collection, presentation in each language. The purpose of this article is to compare, identify the best examples and search for modern grammar writing tools. The results will be used for «Qazaq Grammar», which is planned to be released in 2022.